Exploring augmented reality (AR) in science education: Perspectives from gifted students - Coştu, Fatma (The Journal of educational research (Washington, D.C.), 2025)
This study aims to explore the perspectives of gifted students on augmented reality, one of the innovative possibilities offered by instructional technologies. Action research involved 40 gifted students aged 10-11, enrolled in a Science and Art Center (SAC). Over the course of five weeks, the study focused on teaching various topics related to chemistry, including the structure of atoms, the symbols and applications of elements and compounds, as well as the formation of different compounds and their relevance to everyday life. Augmented reality (AR) applications were utilized for instructional purposes. The findings revealed that the AR applications employed during the study facilitated learning, heightened interest, and curiosity in the subject matter, enhanced the enjoyment and productivity of the lessons, provided a tangible understanding through their three-dimensional representations appealing to multiple senses, and offered a sense of realism by enabling students to interact with virtual objects in real-time.